Evaluation of Antimicrobial Resistance Profiles of Bacteria Isolated from Biofilm in Meat Processing Units - Alexandra Ban-Cucerzan; Adriana Morar; Emil Tîrziu; Kálmán Imre (MDPI AG, 2023)
The aim of this study was to assess the hygiene of pork, beef, and poultry carcasses and to determine the phenotypic antibiotic susceptibility of the bacteria embedded in the biofilm formed on the carcasses kept in cooling chambers for at least three days. The level of hygiene was assessed by determining the total aerobic colony count (TACC) and the Enterobacteriaceae level in different sampling points of the carcasses, along with the detection of E. coli and Pseudomonas spp. embedded in the biofilm. Furthermore, the E. coli and Pseudomonas spp. isolates were tested for antimicrobial resistance profiles. A total of 130 samples collected from pork, beef, and poultry from processing units were analyzed to determine the total aerobic colony count as well as to measure the level of Enterobacteriaceae found on the carcasses. The antimicrobial susceptibility of 44 Escherichia coli and eight Pseudomonas spp. strains isolated from the carcasses were assessed using the Vitek 2 system using two different cards. Overall, the regulatory limits for the TACC were exceeded in 7.6% of the samples, and 65% of the samples exceeded the regulatory limits for Enterobacteriaceae levels. The antimicrobial susceptibility tests of the E. coli isolates analyzed with the AST-GN27 card revealed the highest resistance to be that towards ampicillin (76.1%), followed by cefazolin (71.4%), amoxicillin/clavulanic acid (61.9%), nitrofurantoin (52.3%), cefoxitin (47.6%), tetracycline (38.1%), piperacillin, norfloxacin (19%), trimethoprim-sulfamethoxazole (11.9%), cefotaxime (9.5%), ceftazidime, cefazolin, amikacin, gentamicin, and ciprofloxacin (4.7%). However, all of the isolates were sensitive to piperacillin-tazobactam and imipenem. Thirty-two (61.5%; 95% CI 47.9-73.5) out of fifty-two isolates exhibited multidrug resistance, resulting in the expression of 10 resistance profiles. The findings of this study highlight serious hygienic and sanitary deficiencies within the meat processing units and demonstrate that the resulting meat can harbor Multidrug-resistant Escherichia coli and Pseudomonas spp., both of which pose a serious public health risk. However, further research with a larger number of samples is required to reach thorough results.